CARBON EMISSION DISCLOSURE, ECO-EFFICIENCY, AND FIRM VALUE - Oktaviani, Ayu; Al Ghozi, Muhammad Atho (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
Environmental problems such as global warming that are currently occurring have prompted a shift in business focus that was once profit-oriented, towards a broader orientation by considering environmental aspects as one of the aspects that stakeholders need to pay attention to in making decisions. This study aims to prove that environmental aspects, especially carbon emission disclosure and eco-efficiency practices, can build better firm value. With the population of energy sector companies listed on the Indonesia Stock Exchange in 2019-2023 and multiple linear regression analysis methods, it was found that carbon emission disclosure did not significantly impact the firm value. It shows that the comprehensiveness of carbon emission disclosure has not been a strong signal in changing investors' perception of companies. Inversely proportional to the results of other tests, eco-efficiency, which has a positive and significant influence on the firm value, shows that the company's ability to balance ecological and economic aspects brings a positive and significant signal to the assessment of stakeholders towards a company. The study contributes to the theory and practice of green accounting, namely the disclosure of carbon emissions and eco-efficiency to stakeholders' perception, especially investors in their business decisions.